Factors associated with postpartum depression in women from low socioeconomic level in Argentina: A hierarchical model approach - Pham, Diana (2017)
Purpose to estimate the prevalence of depression at 4-week postpartum using the Edinburgh postpartum Depression Scale (EPDS) in women who delivered in a public maternity hospital in Argentina. Methods This prospective cohort study was carried out from March to August 2016 in northwest Argentina. Eligibility included delivering a singleton live birth 28 weeks of gestational age or over, 18 years or older and resided within 1 h from the maternity hospital. Women were excluded if they or their newborn were in the intensive care unit. We defined a positive screening as an EPDS score of 10 or higher or a positive response to item 10, which indicates thoughts of self-harm. Results A total of 587 women were enrolled and 539 women completed the home visit interview and the EPDS. A total of 167 (31.0%, 95% CI 27.1?35.1) mothers screened positive in the EPDS using a score ≥ 10 and 99 (18.4%, 95% CI 15.1?21.6%) using a score ≥ 13, which indicate increased severity of depressive symptoms. In both cases, the 23 (4.3%) women that responded as having thoughts of self-harm were included. Conclusion Nearly a third of women who participated had depressive symptoms at four weeks postpartum in a public hospital in Tucumán, Argentina. Socio-demographic, particularly personal psychiatric history, factors and social and cultural influences can impact results. Our results highlight the need for improved screening and better diagnostic tool for women with postpartum depression in Argentina and to investigate the impact of postpartum depressive symptoms on women´s health and their families.